(untitled) (Eurasian Research Bulletin, 2022)
Inclusion primarily involves the inclusion of all children in society, because children with disabilities most of all need a friendly educational environment, which at the same time would not be artificial. Programs specially developed for "special" children are implemented in the isolation of boarding schools. Correctional organizations create a closed world for the child, in which attention is focused on his “lack”. An inclusive approach gives children the opportunity to become part of society and live a real life.